Genetic Architecture of Soybean Yield and Agronomic Traits. Issue 10 (1st October 2018) - Diers, Brian W; Specht, Jim; Rainey, Katy Martin; Cregan, Perry; Song, Qijian; Ramasubramanian, Vishnu; Graef, George; Nelson, Randall; Schapaugh, William; Wang, Dechun; Shannon, Grover; McHale, Leah; et al.
Abstract: Soybean is the world's leading source of vegetable protein and demand for its seed continues to grow. Breeders have successfully increased soybean yield, but the genetic architecture of yield and key agronomic traits is poorly understood. We developed a 40-mating soybean nested association mapping (NAM) population of 5, 600 inbred lines that were characterized by single nucleotide polymorphism (SNP) markers and six agronomic traits in field trials in 22 environments. Analysis of the yield, agronomic, and SNP data revealed 23 significant marker-trait associations for yield, 19 for maturity, 15 for plant height, 17 for plant lodging, and 29 for seed mass. A higher frequency of estimated positive yield alleles was evident from elite founder parents than from exotic founders, although unique desirable alleles from the exotic group were identified, demonstrating the value of expanding the genetic base of US soybean breeding.